Immunological Microenvironment Alterations in Follicles of Patients With Autoimmune Thyroiditis - Huang, Ning; Liu, Dandan; Lian, Ying; Chi, Hongbin; Qiao, Jie (Frontiers in Immunology, 2021)
Autoimmune thyroiditis (AIT) is the most prevalent autoimmune endocrine disease, with a higher incidence in women than in men. Immunological abnormalities may lead to the impairment of ovarian folliculogenesis; however, whether the presence of AIT affects immunological microenvironment in follicles remains controversial. We performed a cross-sectional study including 122 patients, aged 20–40 years, who underwent IVF/ICSI treatment owing to isolated male or tube factor infertility. Patients were divided into AIT and control groups according to clinical presentation, thyroid function, and thyroid autoantibody measurements. Follicular fluid was collected and the distribution of cytokines/chemokines in follicular fluid was measured by flow cytometry using multiplex bead assays between the two groups. Based on differences in levels of intrafollicular chemokines and cytokines between the AIT and control groups, the relevant inflammatory cascade was further demonstrated. Among the 12 chemokines analyzed, three (CXCL9, CXCL10, and CXCL11) showed significantly elevated levels in the follicular fluid of patients with AIT. Among the 11 cytokines detected, compared with those in the control group, significantly higher levels of IFNγ were observed in patients with AIT. IFNγ dose-dependently stimulated the expression and secretion of CXCL9/10/11 in cultured primary granulosa cells. The percentage of CXCR3+ T lymphocytes was significantly elevated in the follicular microenvironment of patients with AIT. We concluded that the IFNγ-CXCL9/10/11-CXCR3+ T lymphocyte inflammatory cascade is activated in the follicular microenvironment of patients with AIT. These findings indicate that a considerable immune imbalance occurred in the follicular microenvironment of patients with AIT.